An Ethnomathematical Exploration of Dowry Calculations Based on Social Stratification and the Distribution of Mandar Customary Inheritance for Mathematics Learning - Siti Hardianti; Nurwahida; Buhaerah; Abdillah (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
This study examines the mathematical concept behind the distribution of dowry and inheritance in the BatuLaya village community, Polewali Mandar, West Sulawesi. This study explores the representation of mathematical ideas in cultural traditions passed down between generations, using a qualitative approach framed by ethnomathematicsData were collected through observation, semi-structured interviews, and archival analysis, which included traditional elders, families, and community representatives who were filtered using sampling techniques with certain considerations. Data analysis activities are guided by the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, information presentation, and drawing conclusions. Research findings prove that the determination of dowry in Mandar society is greatly influenced by the social stratification system, which is divided into the lower stratum (tau ata), middle stratum (tau maradika), and noble stratum (tau malaqbi/tau maradia). Each social group has a variety of different traditional assets and equipment, including the Chinese Peputi and Flower Kappu. However, the distribution of inheritance is not determined by social class, but rather based on family agreement, customary values, parental decisions, and religious principles. The study found that the Mandar cultural heritage reflects several mathematical concepts, including proportional reasoning, measurement, multiplication, unit conversion, division, and fractions. These concepts are closely connected to the community's traditional practices, making them suitable for use in contextual mathematics learning. Learning mathematics through local cultural practices helps students relate abstract ideas to familiar experiences and encourages greater appreciation of their own cultural heritage.